PTH-179 An Audit of Clinical outcomes of Sehcat Study in Patients with Chronic Diarrhoea. (4th June 2013) - Kumar, L; Jamshed, B; Emmanuel, A
Abstract : Introduction: Latest NICE guidance suggest that there is not enough evidence to determine whether SeHCAT test is a cost effective option for diagnosing bile acid malabsorption (BAM) among people with IBS-D and Crohn's disease patients without ileal resection. We undertook an audit of sequential patients referred for SeHCAT testing to assess diagnostic value. Methods: Retrospective data was collected from 88 consecutive patients referred to Nuclear Medicine for SeHCAT testing over one year. The indication for the test request and treatment given were collected from request forms, clinic letters and GP record. Subjective global outcome was assessed at mean of 3 months after treatment (range 2–7). Results: Of 88 patients who underwent SeHCAT test, 49 (56%) were found to be positive for bile acid malabsorption. Of these 29 (59%) had severe ( < 5% retention), 9 (18%) had moderate ( > 5 and < 10% retention) and 11 (22%) had mild BAM ( > 10 and < 15% retention) . With regard to the distribution of positive SeHCAT test results according to aetiology, there were 18 patients who fell into BAM Type 1 (Ileal disease/resection) group out of which 17(94%) were positive. Type 2 (Idiopathic BAM) had a total of 57 patients out of which 24(42%) were positive and Type 3 (Secondary to other GI disease) had 13 patients of which 8(62%) tested positive to SeHCAT study. Table 1 below shows the outcomes of bile acid sequestrant (BAS) according to BAM groups. 39/88 (44%) patients had a negative test. Diagnoses were made as follows: IBS-D 13, inflammatory bowel disease with no BAM 8, functional or non-specific diarrhoea 18. In these patients BAS was empirically started, in spite of the test results, in 6, 2 and 5 patients respectively. Only 1 of these 13 (8%) patients (who had IBS-D) improved. Conclusion: Changes in treatment as a result of the SeHCAT test were made in 70% (62/88) of all patients: 84% (41/49) positive patients and 33% (13/39) negative patients. In terms of yield of SeHCAT, patients with chronic diarrhoea and ileal disease (BAM Type 1) may warrant empiric BAS treatment without testing since there was 94% response, suggesting limited value in terms of yield of new information. In contrast, there was value to a negative study, which predicted lack of response (8%) to BAS. Disclosure of Interest: None Declared.